Arab Women’s Autobiography: A Contentious Practice that Elicits Disapprobation, Jeering, Curiosity and/or … Furor - Kholoussi, Samia (Advances in Social Sciences Research Journal, 2019)
Abstract For the Arab female subject, writing against the dominant discourses, the challenges in the autobiographical undertaking have a particular resonance. Regardless of age group, religious and political affiliation, class identification and socio-economic standing, authoring a text about female life is a disconcerting practice. This study is a critical analysis of the tension-ridden arena which female self-narrative occupies and the premises that have for long gone unquestioned, thus rendering the genre unapproachable for Arab women.